Edge Cloud and Mobile Auxiliary Equipment of Fine Art Painting Course Teaching Auxiliary System Design - Huijing Wang (Advances in Multimedia)
Due to the development of information technology, the new type of smart campus integrates teaching, scientific research, office services, and many other applications, and online education information resources show a blowout growth. Art and painting teaching courses in the cloud era also face a series of digital challenges. In view of the development of digital teaching mode, art and painting course is different from other courses and has higher requirements for the transmission of audio and video. How to transmit the audio and video generated during interactive teaching efficiently and with low latency is a challenge. In order to realize the needs of art painting course teaching, based on the characteristics of edge cloud and mobile auxiliary equipment, build the “double cloud” mode of art painting teaching auxiliary system, through the cloud edge deployed different layers and design adaptive code switching mechanism, realize the art painting teaching and remote teaching video flow, help to realize the teaching interaction between teachers and students and instant feedback, and help to improve the art painting course teaching effect.